Developing an Instructional Media of English General Purpose Through Android Based - Ahmad Suhaili; Gema Ika Sari (English Education Department, 2019)
The purpose of this development research is to develop Android applications as a medium for collage school English general-purpose learning in part of speech for collage school students of first semester of STIT AL-KHAIRIYAH. The development model used refers to the development model of research procedures of Dick & Carey. It begins with an analysis of instructional, analysis of learners and context, research instrument of goal performance, selects materials and developing and evaluating application. To obtain a decent animation media used in the first study validated by expert content, media and teacher/lecturer. Furthermore, the students tested media covering the trial of small and large group trials. Test subjects were students of first semester of Non-English learner STIT AL-KHAIRIYAH among 36 students. Results of the assessment or validation shows that (1) validation of learning material expert, media expert and lecturer are on good qualifying with a mean of 80.34%. (2) Small group trial is on good qualifying, reaching level on 76,67% and (3) large group reach at level 80,12%.